The Study of Band Structure of Graphite Intercalation Compound Containing Sodium Calculated Using Density Functional Theory - Rosli, AN; Wahab, IF; Zabidi, NA; Abu Kassim, H (IOP Publishing Ltd, 2024)
Sodium intercalation in graphite (GIC-Na) was investigated by the first principle calculation. The structure of GIC-Na was calculated using density functional theory (DFT) with the aid of CASTEP module of Material Studio. The exchange correlation functional has been treat by local density approximation (LDA) and generalized gradient approximation (GGA). It was shown that, unlike potassium GIC and lithium GIC, the band gap of GIC-Na was not induced and has same value of band gap with bulk graphite.